2018
DOI: 10.1016/j.nucengdes.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition algorithm for analysis of chugging direct contact condensation

Abstract: Direct contact condensation of steam bubbles in a boiling water reactor suppression pool has long been studied utilizing video recording of experiments.The use of video recording enables observation of the behaviour of the bubble surface area and can assist in validation of computational fluid dynamics models.A direct contact condensation experiment of the suppression pool test facility PPOOLEX was recorded using high-speed cameras. The recorded video material was used for development of a pattern recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Error estimation showed that the errors of the volume and surface area remain under 10 %, when the diameter of the bubble is under 13 cm. For really small bubbles (d < 4.0 cm) errors may build up over 20 %, but otherwise lay between 10 to 20 %, (Hujala et al, 2018). However, the uncertainty caused by these systematic errors should remain small in this study, because the bubble size difference between successive frames is more important than the absolute size of a bubble.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Error estimation showed that the errors of the volume and surface area remain under 10 %, when the diameter of the bubble is under 13 cm. For really small bubbles (d < 4.0 cm) errors may build up over 20 %, but otherwise lay between 10 to 20 %, (Hujala et al, 2018). However, the uncertainty caused by these systematic errors should remain small in this study, because the bubble size difference between successive frames is more important than the absolute size of a bubble.…”
Section: Resultsmentioning
confidence: 83%
“…DCC-05 experiment was one part of the direct contact condensation test program. The main purpose of the DCC-05 was to obtain measurement data for the validation of the DCC models used in CFD, and to make a high-speed video recording to be used in the development work of the pattern recognition algorithm (Hujala, 2013;Hujala et al, 2018). The aim of the DCC-05 experiment was to keep the pool water temperature as constant as possible and change the steam flow rate in a wide range.…”
Section: Ppoolex Test Facility and Dcc-05 Experimentsmentioning
confidence: 99%
See 3 more Smart Citations